Neurobiological mechanisms mediating emotion dysregulation as targets of change in borderline personality disorder - Herpertz, Sabine; Schneider, Isabella; Schmahl, Christian; Bertsch, Katja (Psychopathology, 2018)
Emotion dysregulation is a hallmark of borderline personality disorder (BPD). Most interventions for patients with BPD, therefore, aim at the improvement of emotion regulation. In the current paper, we provide an overview of studies investigating the effects of psychotherapeutic or pharmacological interventions on neurobiological correlates of various aspects of emotion regulation. In fact, studies suggest that the prefrontal-limbic circuit may play a major role in mediating effects of clinically efficacious psychotherapeutic treatments, i.e., they lead to clinical improvement via modulating the function and structure of the amygdala, the insula, and the dorsal anterior cingulate cortex, as well as prefrontal areas involved in the cognitive regulation of emotions, and enhancing the coupling of limbic and prefrontal areas. Oxytocin as a promising pharmacological approach to emotion dysregulation in BPD was shown to dampen amygdala activity in response to emotional stimuli. Understanding the brain mechanisms that mediate treatment effects will harness further development of targeted mechanism-based interventions for patients with BPD.
Published online: April 19, 2018
Gesehen am 19.12.2019